(untitled) (Asian Journal of Medical Sciences, 2014)
The Sprengel’s deformity is a congenital condition where the scapula on one or both sides are underdeveloped or abnormally high in position. An interesting rare case of Sprengel’s deformity and unilateral absent kidney is being reported. The Sprengel’s deformity should not be left undiagnosed. DOI: http://dx.doi.org/10.3126/ajms.v5i4.9494 Asian Journal of Medical Sciences 2014 Vol.5(4); 97-99